1989
DOI: 10.1007/bf00441955
|View full text |Cite
|
Sign up to set email alerts
|

Long-term outcome of lithium prophylaxis in patients initially classified as complete responders

Abstract: The long-term outcome of lithium prophylaxis was explored in 43 bipolar and 36 unipolar patients who had been classified as complete responders after the first 2 years of treatment. These patients were followed up prospectively for a further period of 5 years (treatment period II), during which their psychopathological state was assessed monthly or bimonthly. Forty-nine patients completed treatment period II, 2 died during this period, 7 did not attend the unit any more and could not be traced, and 21 definiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
42
0
3

Year Published

1991
1991
2010
2010

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(49 citation statements)
references
References 19 publications
4
42
0
3
Order By: Relevance
“…Furthermore, clinical variables such as episode sequence (Kokopolus et al, 1980;Maj et al, 1989), frequency of mood cycling (Dunner and Fieve, 1974;Bowden 1995;Denicoff et al, 1997), presence of mood-congruent or -incongruent psychotic features of the index episode (Greil et al, 1998;Tohen et al, 1992), comorbid conditions (especially anxiety disorders) (Greil et al, 1998;Feske et al, 2000), and family history (Grof et al, 1994) may provide further explanation of the differential response to lithium and divalproex. Some of these may need to be described in future studies as potential explanatory factors of treatment response.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, clinical variables such as episode sequence (Kokopolus et al, 1980;Maj et al, 1989), frequency of mood cycling (Dunner and Fieve, 1974;Bowden 1995;Denicoff et al, 1997), presence of mood-congruent or -incongruent psychotic features of the index episode (Greil et al, 1998;Tohen et al, 1992), comorbid conditions (especially anxiety disorders) (Greil et al, 1998;Feske et al, 2000), and family history (Grof et al, 1994) may provide further explanation of the differential response to lithium and divalproex. Some of these may need to be described in future studies as potential explanatory factors of treatment response.…”
Section: Discussionmentioning
confidence: 99%
“…Strategies for treatment often become more complex and a variety of combinations of mood stabilisers are often used, principally because resistance to monotherapy may increase with time. 71 Indeed, it has been suggested that the elderly reflect a largely resistant subgroup. 1 The use of adjunctive therapy raises the issue of safety and pharmacokinetic interactions, and long-term safety issues will need to be investigated in the elderly.…”
Section: Implications For Researchmentioning
confidence: 99%
“…There is increasing recognition of the inadequacy of "lithium treatment" in bipolar illness, even with adjunctive antidepressants and neuroleptics (Maj et al 1989;Aagaard and Vestergaard 1990;O'Connell et al 1991;Vestergaard 1992;Gitlin et al 1995). Some bipolar patient subtypes are particularly prone to lithium nonresponsiveness; among these are patients with dysphoric mania and rapid cycling; a negative family history for bipolar illness in first-degree relatives; the episode sequence pattern of depression-mania-well interval (i.e., the D-M-I pattern as opposed to the M-D-I pattern); more than three episodes prior to the initiation of prophylaxis (Sarantidis and Waters 1981;O'Connell et al 1991;Denicoff et al 1997); a history of co-morbid substance abuse; and those patients with a history of head trauma or other such medical co-morbidities as multiple sclerosis, etc.…”
mentioning
confidence: 99%
“…In addition, it is recognized that patients with initial excellent responses to lithium can begin to develop breakthrough episodes in subsequent extended years of follow-up (Maj et al 1989;Post et al 1992). In our series of 66 lithium-refractory patients, 23 (34.9%) seem to have developed their lithium-refractoriness over more prolonged periods of follow-up, in a pattern resembling tolerance.…”
mentioning
confidence: 99%